The super natural : why the unexplained is real - Strieber, Whitley; Kripal, Jeffrey J. (Jeffrey John), 1962- (A TarcherPerigee Book, 2017)
Whitley Strieber (Communion) and Jeffrey J. Kripal (J. Newton Rayzor professor of religion at Rice University) team up on this unprecedented and intellectually vibrant new framing of inexplicable events and experiences. Rather than merely document the anomalous, these authors--one the man who popularized alien abduction and the other a renowned scholar and "renegade advocate for including the paranormal in religious studies" (The New York Times)--deliver a fast-paced and exhilarating study of why the supernatural is neither fantasy nor fiction but a vital and authentic aspect of life. Their suggestion? That all kinds of "impossible" things, from extra-dimensional beings to bilocation to bumps in the night, are not impossible at all: rather, they are a part of our natural world. But this natural world is immeasurably more weird, more wonderful, and probably more populated than we have so far imagined with our current categories and cultures, which are what really make these things seem "impossible." The Super Natural considers that the natural world is actually a "super natural world"--and all we have to do to see this is to change the lenses through which we are looking at it and the languages through which we are presently limiting it. In short: The extraordinary exists if we know how to look at and think about it.